Mechanism of Action of Mycotoxins - García, Cristina Juan (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Mycotoxins are a diverse group of chemicals that present wide toxicological responses in animals and humans. Their ingestion causes toxic effects that go from acute toxicity to long-term or chronic health disorders. Some mycotoxins have caused outbreaks of human toxicoses, and at least one mycotoxin, aflatoxin B1, is an assumed human hepatocarcinogen. As part of a comprehensive effort to curtail the adverse health effects posed by mycotoxins, substantial research has been conducted to determine the mechanism of action of mycotoxins. Although much information has been obtained regarding the action of several mycotoxins, future research topics should continue to address several areas of critical concern.In vitro studies in different cell lines could detail and explain many of these mechanisms, while in vivo can give a real scenario in the development of a toxic effect. This Special Issue of Toxins collected the most recent reports on the mechanism of action of mycotoxins on single or combined mycotoxins studied in vivo or in vitro, the identification of known and unknown mycotoxins metabolites and other metabolites in different cell lines and animals or matrices (including organs, urine, or blood), and the development of analytical skills to study these mechanisms. A total of eleven papers, eight research papers and three review articles, are included in this reprint.